Native and Target Language Influence on Students’ Interlanguage Speech - Dika Pratiwi, Putu; Sri Adnyani, Ni Luh Putu; Adi Jaya Putra, I Nyoman (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2020)
Literature confirms that various errors made by Indonesian learners of English as a foreign language are challenging phenomenon which needs our concern. The errors found are both in speech and composition production, which portray the effectiveness of language learning. Students language that belongs neither native nor target language is called interlanguage (IL). The focus of this study is to present the empirical results of the investigation on the IL features of students' speech production. It aims to describe the types and aspects of the native language (NL) and target language (TL) influences and to explain the possible causes of IL production. The data were in the form of 144 ill-formed utterances. In gathering the data, the students were given a guided picture with the topic ‘Last Holiday’. The students' speech was video recorded.  The ill-formed utterances were collected, identified, described, and explained. The result of the study shows that both of their NL and TL influenced the students' interlanguage production at the syntactical level.